Microorganismos prevalentes en prótesis totales, aparatología ortopédica y sus manifestaciones orales. Reporte de literatura 2014 - 2020 (2021)
Orthotics and prostheses are artificial elements that are responsible for replacing lost teeth, returning functionality and aesthetics of the patient, due to anatomical, genetic or oral hygiene problems, contributing to the proliferation of microorganisms and bacterial plaque in the devices. acrylics